Impact Of Social Media On Consumers Brand Preference For Laptops - et. al., Dr.Muskan Nagi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increasing demand of Internet/Online based social media has made it with easy for people to communicated with hundreds not even hundreds but also thousands of people to communicate about the product and companies that provide them. In the market place impact of customer to customer communication has greatly been magnified. The current study focuses on social media impact on consumer brand preference (product or services) and consumer behaviour. The study is conducted to understand the impact of social media on consumer brand for purchasing laptops. There were 100 respondents from chandigarh, India. The analysis is done with help of t- Test and regression analysis. The study results as a significant impact of social media on consumer brand preference for Laptop purchasing.